2020
DOI: 10.1002/da.23107
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cognitive‐behavioral therapy and yoga for the treatment of late‐life worry: A randomized preference trial

Abstract: Background: The purpose of this study was to compare the effects of cognitivebehavioral therapy (CBT) and yoga on late-life worry, anxiety, and sleep; and examine preference and selection effects on these outcomes. Methods: A randomized preference trial of CBT and yoga was conducted in community-dwelling adults 60 years or older, who scored 26 or above on the Penn State Worry Questionnaire-Abbreviated (PSWQ-A). CBT consisted of 10 weekly telephone sessions. Yoga consisted of 20 biweekly group yoga classes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…It was reported that symptoms of insomnia declined, on average, among participants in both interventions; however, those in the CBT intervention demonstrated a significantly greater improvement in sleep than NST over a 12-month follow-up period. A later, large randomized preference trial by Brenes et al (2020) extended these findings in a trial comparing CBT-T with yoga for the treatment of worry in older adults. Study findings suggest that CBT-T was significantly superior to yoga in reducing scores on the ISI, although both interventions did produce improvements in insomnia symptoms, worry and anxiety.…”
Section: Studies Assessing Cbt Interventions For Late-life Depressionmentioning
confidence: 91%
See 1 more Smart Citation
“…It was reported that symptoms of insomnia declined, on average, among participants in both interventions; however, those in the CBT intervention demonstrated a significantly greater improvement in sleep than NST over a 12-month follow-up period. A later, large randomized preference trial by Brenes et al (2020) extended these findings in a trial comparing CBT-T with yoga for the treatment of worry in older adults. Study findings suggest that CBT-T was significantly superior to yoga in reducing scores on the ISI, although both interventions did produce improvements in insomnia symptoms, worry and anxiety.…”
Section: Studies Assessing Cbt Interventions For Late-life Depressionmentioning
confidence: 91%
“…Three trials examined the effects of telephone CBT (CBT-T) on sleep disturbance in participants with late-life GAD (Brenes et al, 2016(Brenes et al, , 2020(Brenes et al, , 2012. In the Brenes et al (2012) study, scores on the ISI suggested greater improvements in insomnia severity in the CBT-T group post-intervention, relative to the information-only control condition, but in a similar trend to other clinical measures, this differential treatment effect was not maintained at the 6-month follow-up period.…”
Section: Studies Assessing Cbt Interventions For Late-life Depressionmentioning
confidence: 99%
“…The first outcomes evidence on the efficacy of the Relax into Yoga program found that it was effective for improving worry, anxiety and sleep among worried older adults. [22] With safety principles at the heart of our approach, the word "relax" is explicitly used in the title to highlight an important distinction about initiating and sustaining yoga practice that is particularly relevant to seniors. A key characteristic that differentiates this ancient approach to wholeness from modern exercise is the importance of moving to a point of challenge, but not strain.…”
Section: The Integrative Yoga For Seniors Program At Duke Integrative Medicine: Perspectives From 13 Years Of Professional Trainingsmentioning
confidence: 99%
“…Findings from previously published analyses of primary and secondary outcomes showed that CBT and yoga were both effective at reducing worry and anxiety, and a greater impact was seen for CBT compared with yoga for improving sleep. 8 The focus of this investigation is on a variety of prevalent and interrelated symptoms commonly reported by older adults with substantial worry: depressive symptoms, generalized anxiety symptoms, fatigue, and pain.…”
Section: Introductionmentioning
confidence: 99%
“…As reported above, findings for the primary outcome (worry) and secondary outcomes (anxiety, sleep) have been published elsewhere. 8 In this secondary data analysis using data from the randomized arm (N = 250), we compared the effects of CBT and yoga on several exploratory outcomes: depressive symptoms, generalized anxiety symptoms, fatigue, pain interference, pain intensity, physical function, and social participation. Using data from both the randomized and preference trial arms (N = 500), we examined the effects of preference (i.e., an effect on outcome from having a choice in treatments compared with being randomized) and selection (i.e., an effect on outcomes by making a specific treatment choice ) on depressive symptoms, generalized anxiety symptoms, fatigue, pain interference, pain intensity, physical function, and social participation.…”
Section: Introductionmentioning
confidence: 99%